FveARF2 negatively regulates fruit ripening and quality in strawberry - Yi, Shan-na; Mao, Jian-xin; Zhang, Xin-yu; Li, Xiao-ming; Zhang, Zhi-hong; Li, He (Frontiers in Plant Science, 2022)
Auxin response factors (ARFs) are transcription factors that play important roles in plants. ARF2 is a member of the ARF family and participates in many plant growth and developmental processes. However, the role of ARF2 in strawberry fruit quality remains unclear. In this study, FveARF2 was isolated from the woodland strawberry ‘Ruegen’ using reverse transcription-polymerase chain reaction (RT-PCR), which showed that FveARF2 expression levels were higher in the stem than in other organs of the ‘Ruegen’ strawberry. Moreover, FaARF2 was higher in the white fruit stage of cultivated strawberry fruit than in other stage. Subcellular localization analysis showed that FveARF2 is located in the nucleus, while transcriptional activation assays showed that FveARF2 inhibited transcription in yeast. Silencing FveARF2 in cultivated strawberry fruit revealed earlier coloration and higher soluble solid, sugar, and anthocyanin content in the transgenic fruit than in the control fruit, overexpression of FveARF2 in strawberry fruit delayed ripening and lower soluble solid, sugar, and anthocyanin content compared to the control fruit. Gene expression analysis indicated that the transcription levels of the fruit ripening genes FaSUT1, FaOMT, and FaCHS increased in FveARF2-RNAi fruit and decreased in FveARF2-OE fruit, when compared with the control. Furthermore, yeast one-hybrid (Y1H) and GUS activity experiments showed that FveARF2 can directly bind to the AuxRE (TGTCTC) element in the FaSUT1, FaOMT, and FaCHS promoters in vitro and in vivo. Potassium ion supplementation improved the quality of strawberry fruit, while silencing FveARF2 increased potassium ion content in transgenic fruit. The Y1H and GUS activity experiments also confirmed that FveARF2 could directly bind to the promoter of FveKT12, a potassium transporter gene, and inhibited its expression. Taken together, we found that FveARF2 can negatively regulate strawberry fruit ripening and quality, which provides new insight for further study of the molecular mechanism of strawberry fruit ripening.